Celecoxib reduces Deoxynivalenol induced proliferation, inflammation and protein kinase C translocation via modulating downstream targets in mouse skin. (1st August 2020) - Mishra, Sakshi; Srivastava, Sonal; Divakar, Aman; Mandal, Payal; Dewangan, Jayant; Chaturvedi, Swati; Wahajuddin, Muhammad; Kumar, Sadan; Tripathi, Anurag; Rath, Srikanta Kumar
Abstract: Exposure to mycotoxins is mostly by ingestion but also occurs by the dermal and inhalation routes. The present study for the first time demonstrated that mycotoxin Deoxynivalenol (DON), permeates through Swiss albino mice skin, which demands awareness of health risks in people who are dermally exposed to mycotoxins especially agricultural farmers. Despite the widespread contamination of DON in food commodities studies to alleviate DON's toxicity are sparsely reported. Thus effective measures to combat mycotoxins associated toxicity remains an imperative aspect to be considered from the angle of dermal exposure. Topical application of Celecoxib (1–2 mg), followed by DON (100 μg) application on the dorsal side of mice, resulted in substantial decrease in DON-induced (i) edema, hyperplasia, cell proliferation (ii) inhibition of cytokine and prostaglandin-E2 levels (iii) phosphorylation of ERK1/2, JNK, p38, MAPKKs, CREB, P90-RSK (iv) downregulation of c-Jun, c- Fos, phospho-NF-kB and their downstream target proteins cyclin D1 and COX-2. Using Ro-31-8220 (Protein-Kinase-C inhibitor), it was observed PKC was responsible for DON induced upregulation of COX-2 and iNOS proteins. Treatment of Celecoxib decreased DON-induced translocation of Protein Kinase C isozymes (α, ε, γ), demonstrating the role of PKC in DON-mediated biochemical and molecular alterations responsible for its dermal toxicity. The present findings indicate that topical application of celecoxib is effective in the management of inflammatory skin disorders induced by foodborne fungal toxin DON. The skin permeation potential of Celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor NSAID, was also assessed, and the results indicated that the permeation was relatively lower as compared to the oral mode of administration. Hence topical use of celecoxib may be preferred over oral dosing because of lower systemic absorption and to avoid the unwanted side effects. This study provides a prospect for exploring the clinical efficacy of topically applied COX-2 inhibitors for the management of inflammatory skin disorders induced by foodborne fungal toxins. Graphical abstract: Image 1 Highlights: Deoxynivalenol (DON), a trichothecene mycotoxin penetrates through mice skin. Protein Kinase C is involved in DON induced upregulation of COX2 and iNOS proteins. Celecoxib reduces DON induced epidermal inflammation and cell proliferation. Skin Permeation potential of Celecoxib, is lower as compared to the oral route. Celecoxib can effectively ameliorate mycotoxin induced skin inflammatory disorders.